Les métropoles créent-elles plus d’emplois ? - John Baude (EchoGéo)
Employment growth was stronger in metropolitan areas than in other large urban areas in France during the 1980s then again in the 2000s. Several explicative factors, including size, are tested. But the size of the metropolitan areas only contributed to this economic momentum during the first half of the 2000s. Depending on the period, the specialization of their economy by function has either boosted employment, had no impact at all, or conversely had a detrimental impact. However, hysteresis effect is an increasingly important factor, which has widened disparities between regions. Along the Atlantic and Mediterranean coasts and in the Rhône-Alpes region, most of the large urban areas, as well as the metropolitan areas, boast dynamic economies.